Heterotrophic cultivation of microalgae: production of metabolites of commercial interest. Issue 5 (24th October 2016) - Morales‐Sánchez, Daniela; Martinez‐Rodriguez, Oscar A; Martinez, Alfredo
Abstract: Several microalgal species are capable of growing heterotrophically, exhibiting considerable metabolic versatility and flexibility. As demonstrated in this review, heterotrophic conditions can enhance the biomass concentration by as much as 25‐fold compared with phototrophic conditions. Currently, these types of cultivation are economically feasible only for high‐value products, including polyunsaturated fatty acids (PUFAs), pigments, antioxidants, polysaccharides, food and aquaculture feed from carbon sources, such as glucose, acetate or glycerol. To make heterotrophic cultivation economically viable for high‐volume, low‐value commodities, such as biofuels, the use of unconventional carbon sources, such as food and agricultural wastes and wastewater, is recommended. Since microalgae are capable of modifying their metabolism according to varying culture conditions, it is possible to modify, control and therefore maximize the production of target compounds. This manuscript not only offers a review of the most relevant and recent findings in the use of heterotrophic microalgal cultivation for enhanced metabolite production but also provides recommendations for future research on this promising subject. © 2016 Society of Chemical Industry